Implicações jurídico-ambientais da água de lastro no complexo portuário de São Luís-MA - GALVÃO, Elisangela Cristina Ribeiro (2015)
Ballast water in several countries has caused damage to the marine environment, health and the economy. With this research approach is the potential environmental risks posed by this type of product dumped in coastal environmental system, with the object of investigation the transition relation between land and sea, characterized as an environment susceptible to several factors of risk by the water discharged from ships is danger to the environment, in that it could jeopardize the fauna and native aquatic flora where water is poured and will interfere with the development of marine species, in addition to transport of endemic diseases. In light of the significant increase in the movement of ships in the bay of São Marcos and the port system of the city of Sao Luis - MA, the concern is necessary and providential, given the significant local biodiversity, and taking into account the interdependence between trade countries is of paramount importance to analyze this problem, noting international treaties and agreements so as to minimize environmental damage and civil society. The overall objective of the study was to demonstrate that this threat is constant in our seas and oceans, seeing the effectiveness of checks on ballast water management in the local context, national and international. The methodological research support includes the study: hypothetical-deductive, with a qualitative approach, including exploratory and descriptive research, through interviews maritime authority, document and literature review. The control and mitigating the effects of ballast water are dependent on the effectiveness of legislative applicability of law, in particular international environmental law in line with the port activity, as a legal instrument for protection of the coastal environment.